Disturbed sleep after lung transplantation is associated with worse patient-reported outcomes and chronic lung allograft dysfunction - Aric A. Prather, PhD; Ying Gao, MS; Legna Betancourt, BS; Rose C. Kordahl, BS; Anya Sriram, BS; Chiung-Yu Huang, PhD; Steven R. Hays, MD; Jasleen Kukreja, MD; Daniel R. Calabrese, MD; Aida Venado, MD; Bhavya Kapse, PhD; John R. Greenland, MD, PhD; et al. (JHLT Open, 2025)
Background: Many lung transplant recipients fail to derive the expected improvements in health-related quality of life (HRQL) and survival. Sleep may represent an important, albeit rarely examined, factor associated with lung transplant outcomes. Methods: Within a larger cohort study, 141 lung transplant recipients completed the Medical Outcomes Study Sleep Problems Index (SPI) Revised scale along with a broader survey of patient-reported outcome (PRO) measures and frailty assessment. From the SPI, we also derived an insomnia-specific subscale. Potential perioperative risk factors for disturbed sleep were derived from medical records. We investigated associations between perioperative predictors on SPI and insomnia and associations between SPI and insomnia on PROs and frailty by linear regressions, adjusting for age, sex, and lung function. We evaluated the associations between SPI and insomnia on time to chronic lung allograft dysfunction (CLAD) and death using Cox models, adjusting for age, sex, and transplant indication. Results: Post-transplant hospital length of stay >30 days was associated with worse sleep by SPI and insomnia (SPI: p = 0.01; insomnia p = 0.02). Worse sleep by SPI and insomnia was associated with worse depression, cognitive function, HRQL, physical disability, health utilities, and Fried Frailty Phenotype frailty (all p < 0.01). Those in the worst quartile of SPI and insomnia exhibited an increased risk of CLAD (hazard ratio [HR] 2.18; 95% confidence interval [CI]: 1.22-3.89; p = 0.01 for SPI and HR 1.96; 95%CI 1.09-3.53; p = 0.03 for insomnia). Worsening in SPI but not insomnia was also associated with mortality (HR: 1.29; 95%CI: 1.05-1.58; p = 0.01). Conclusions: Poor sleep after lung transplant appears associated with PROs, frailty, CLAD, and death. Clarifying the nature of this association may have important screening implications.